Potential evapotranspiration estimation and its effect on hydrological model response - Nghi, Vu Van; Dung, Do Duc; Lam, Dang Thanh (Vietnam Journal of Mechanics, 2008)
Potential evapotranspiration can be directly calculated by the Penman-Monteith equation, known as the one-step method. The approach requires data on the land cover and related-vegetation parameters based on AVHRR and LDAS information, which are available in recent years. The Nong Son basin, a sub-catchment of the Vu Gia-Thu Bon basin in the Central Vietnam, is selected for this study. To this end, NAM model was used; the results obtained show that the NAM model has the potential to reproduce the effects of potential evapotranspiration on hydrological response. This is seemingly manifested in the good agreement between model simulation of discharge and the observed at the stream gauge.